2010
DOI: 10.1111/j.1476-5829.2010.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of doxorubicin-based chemotherapy for non-resectable canine subcutaneous haemangiosarcoma

Abstract: Eighteen dogs with measurable subcutaneous haemangiosarcoma (SQHSA) were treated with doxorubicin-based chemotherapy. Response assessment was evaluated and compared using World Health Organization (WHO), Response Evaluation Criteria in Solid Tumours (RECIST) and tumour volume criteria. The overall response rate for all dogs was 38.8% using WHO criteria, 38.8% using RECIST criteria and 44% using tumour volume criteria. One dog had a complete response. The median response duration for all dogs was 53 days (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
(96 reference statements)
2
26
0
Order By: Relevance
“…The mainstay of treatment consists of surgery followed by adjuvant intravenous chemotherapy . Doxorubicin‐based chemotherapy protocols have been administered to dogs with HSA, including doxorubicin as single agent, or combined with ifosfamide, vincristine and cyclophosphamide, and epirubicin as single agent . Although doxorubicin is usually administered every 3 weeks, one study attempting to increase dose intensity by more frequent administrations showed such strategy to be well tolerated, although without improved survival time .…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of treatment consists of surgery followed by adjuvant intravenous chemotherapy . Doxorubicin‐based chemotherapy protocols have been administered to dogs with HSA, including doxorubicin as single agent, or combined with ifosfamide, vincristine and cyclophosphamide, and epirubicin as single agent . Although doxorubicin is usually administered every 3 weeks, one study attempting to increase dose intensity by more frequent administrations showed such strategy to be well tolerated, although without improved survival time .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the cases of inoperable cardiac tumours, or those patients for which surgery is an unfavourable option, the consideration of systemic therapy alone as a reasonable secondary option is warranted. Two studies evaluating the utility of DOX‐based chemotherapy protocols for dogs with macroscopic non‐cardiac HSA reported encouraging response rates of 38 and 47% . More recently, an MST of 140 days was reported for dogs treated with various DOX‐based protocols for measureable right atrial tumours .…”
Section: Introductionmentioning
confidence: 99%
“…3 The RECIST guidelines are being adopted in veterinary oncology, leading to reconsideration of methods of screening for abdominal disease and determining response to therapy. [4][5][6] In a study of sonographic measurement of urinary bladder tumors, there was poor to fair correlation between operators, causing misclassification of tumors in terms of response to treatment or progression of disease. 4 There is also a similar variation in intra-and interobserver measurement of lymph nodes.…”
Section: Introductionmentioning
confidence: 99%